Process evaluation of the 'Lafiyan Yara' project on enhancing access to HIV testing services using existing community structures in Nigeria - Olujide Arije; Rachel Titus; Idowu Omisile; Aisha Dadi; Danjuma Garba; Omoregie Godpower; Jennifer Anyanti; Omokhudu Idogho; Emeka Okeke; Carmen Roebersen; Eliane Vrolings; Adedeji Onayade (BMC, 2024)
Abstract Background The Lafiyan Yara Project aimed to increase demand for HIV counselling, testing, treatment, and prevention services among pregnant women and children in Taraba State, Nigeria. Implemented from 2019 to 2021, the project utilized existing community structures, including traditional birth attendants, village health workers, and patent and proprietary medicine vendors, for mobilization. This study assessed the project's activities, contributors, relevance, effectiveness, and efficiency. Methods The process evaluation was conducted using focus group discussions and key informant interviews with beneficiaries, community leaders, project staff, health facility personnel, and government officials. Data analysis employed framework analysis. Results The Lafiyan Yara project was reported to have achieved notable successes, including increased HIV testing rates among children and pregnant women, improved linkage to care services, reduced mother-to-child transmission of HIV, increased HIV/AIDS awareness and knowledge, and enhanced community engagement and support. Challenges identified included insufficient funding for community mobilizers, training needs for health workers, and inadequate availability of test kits at health facilities. Confidentiality and stigma issues arose during community mobilizations. A key lesson learned was the importance of a comprehensive HIV care approach, emphasizing testing and ensuring support for individuals testing positive. Conclusions The project's approach of leveraging community structures to create demand for HIV services among women and children proved effective, provided proper linkage to care for those testing positive. Addressing stigma and involving husbands/fathers in the community approach are crucial for improving outcomes. Trial registration IPHOAU/12/1384.